2020
DOI: 10.29219/fnr.v64.3751
|View full text |Cite
|
Sign up to set email alerts
|

Bile salt hydrolase-overexpressing Lactobacillus strains can improve hepatic lipid accumulation in vitro in an NAFLD cell model

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) includes a range of liver diseases that occur in the absence of significant alcohol consumption. The probiotic bacterial strains Lactobacillus casei LC2W, which overexpresses the bile salt hydrolase (BSH) gene (referred to as pWQH01), and Lactobacillus plantarum AR113, which exhibits high BSH activity, have been shown to improve hepatic lipid accumulation and may lower cholesterol levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Several probiotic strains have been extensively studied and their benefits to human health have been widely documented. For example, it has been reported that probiotics, such as Bifidobacterium longum , Lactobacillus acidophilus , L. casei, L. plantarum , exhibit bile salt hydrolases ( 42 , 72 74 , 80 , 81 ). For example, L. casei pWQH01, which overexpresses bsh 1 from L. plantarum AR113, appear to improve steatosis in vitro in a BSH-dependent manner ( 81 ).…”
Section: Probiotics Diversely Involved In Lipid Metabolism To Improve...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several probiotic strains have been extensively studied and their benefits to human health have been widely documented. For example, it has been reported that probiotics, such as Bifidobacterium longum , Lactobacillus acidophilus , L. casei, L. plantarum , exhibit bile salt hydrolases ( 42 , 72 74 , 80 , 81 ). For example, L. casei pWQH01, which overexpresses bsh 1 from L. plantarum AR113, appear to improve steatosis in vitro in a BSH-dependent manner ( 81 ).…”
Section: Probiotics Diversely Involved In Lipid Metabolism To Improve...mentioning
confidence: 99%
“…For example, it has been reported that probiotics, such as Bifidobacterium longum , Lactobacillus acidophilus , L. casei, L. plantarum , exhibit bile salt hydrolases ( 42 , 72 74 , 80 , 81 ). For example, L. casei pWQH01, which overexpresses bsh 1 from L. plantarum AR113, appear to improve steatosis in vitro in a BSH-dependent manner ( 81 ). Lactobacillus gasseri BNR17 can inhibit the secretion of adiponectin and leptin, and reduce adipose tissue, while L. gasseri SBT2055 reduced mesenteric tissue mass, serum leptin levels and adipocyte size in lean Zucker mice ( 82 , 83 ).…”
Section: Probiotics Diversely Involved In Lipid Metabolism To Improve...mentioning
confidence: 99%
“…Other probiotics, tested either in combination or isolated, also showed beneficial effects on NAFLD improvement [ 45 , 46 ]. Recently, Huang et al demonstrated that Lactobacillus plantarum AR113 and L. casei pWQH0, which both display high BSH activity, decrease hepatic lipid accumulation in NAFLD cell models, which is potentially mediated by the BSH activity [ 47 ]. Besides cholesterol and lipid metabolism, BSH activity may be linked to inflammatory disorders.…”
Section: Bsh In Health and Diseasementioning
confidence: 99%
“…However, the mechanism behind the hypocholesterolemic ability of probiotics remains elusive. Yet one of the most reported mechanism has been attributed to the ability of some probiotics to produce bile salt hydrolase (BSH; Jones et al, 2012 ; Wang et al, 2019a ; Huang et al, 2020 ). Many probiotic bacteria, such as L. plantarum WCFS1, L. plantarum TH1, and Bifidobacteria longum SBT2928, produce BSH ( Ishimwe et al, 2015 ), which can hydrolyze conjugated bile salts, such as taurine-conjugated bile salts and glycine-conjugated bile salts, to release primary bile acids ( Li et al, 2020 ).…”
Section: Probiotic Effector Molecules That Affect Cholesterol-lowerinmentioning
confidence: 99%